Pendidikan Kewarganegaraan Sebuah Jati Diri Bangsa - Apri Sri Rahayu; Gina Mulia Putri; Nur Azizah; Gita Ramadani; Leddy Khairunnisa, Helfira Citra (CV. ITTC INDONESIA, 2024)
Citizenship education for a national identity has values related to the development of national character and national identity. Some of the values contained in citizenship education are religiosity, honesty, intelligence, toughness, solidarity, democracy, nationalism and partisanship. Citizenship education has a fundamental role in shaping the ident!ity of the Indonesian nation. Through citizenship education, the noble values that are the foundation of national character can be instilled and strengthened in every citizen. One of the important values taught is Pancasila, as the basis of the state and the nation's way of life. Pancasila contains five main principles, namely divinity, humanity, unity, democracy and justice, which serve as guidelines for all citizens in their attitudes and behavior. Citizenship education for a national identity has values related to the development of national character and national identity. Some of the values contained in citizenship education are religiosity, honesty, intelligence, toughness, solidarity, democracy, nationalism and partisanship. Efforts for Citizenship Education for a nation's identity are conscious and planned efforts to make the nation's life more intelligent for citizens by cultivating national identity and morals as a basis for implementing rights and obligations in defending the country, for the sake of the continuity of life and glory of the nation and state. Citizenship education for a national identity has values related to the development of national character and national identity. Some of the values contained in citizenship education are religiosity, honesty, intelligence, toughness, solidarity, democracy, nationalism and partisanship